2002
DOI: 10.1046/j.0042-9007.2001.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human ABO gene promoter in erythroid cell lineage

Abstract: The expression of the ABO promoter appears to be influenced by the binding of Sp1 or Sp1-like protein(s) in both erythroid and epithelial cell lineages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 25 publications
1
62
0
Order By: Relevance
“…However, a cell-type-specific promoter has been demonstrated at the 5Ј boundary of the CpG island, although its role remains obscure. Furthermore, 4 tandem copies of a 43-bp repeat unit located 3.8 kb upstream of transcription starting exon 1 driven by the proximal promoter have been shown to have enhancer activity in human gastric cancer KATOIII cells, but not in human erythroleukemia HEL cells, 11,14 suggesting that the enhancer potential of this element is dependent on cell type. Recently, genomewide approaches for the discovery of enhancers have become available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a cell-type-specific promoter has been demonstrated at the 5Ј boundary of the CpG island, although its role remains obscure. Furthermore, 4 tandem copies of a 43-bp repeat unit located 3.8 kb upstream of transcription starting exon 1 driven by the proximal promoter have been shown to have enhancer activity in human gastric cancer KATOIII cells, but not in human erythroleukemia HEL cells, 11,14 suggesting that the enhancer potential of this element is dependent on cell type. Recently, genomewide approaches for the discovery of enhancers have become available.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the human ABO gene using cultured cells have demonstrated transcriptional regulatory elements. [11][12][13][14][15][16][17] A proximal promoter and a negative regulatory region just upstream from it have been found within the ABO CpG island. The proximal promoter is rich in CpG and shows no apparent tissue specificity.…”
Section: Introductionmentioning
confidence: 99%
“…A proximal promoter has been found within the ABO CpG island (CGI) (9,10). However, a cell type-specific, distal promoter has been demonstrated at the 5Ј boundary of the CGI, although the amount of transcript from this promoter was very small (3).…”
mentioning
confidence: 99%
“…The association between the ABO blood groups and various diseases has been a subject of great interest, 8 and approximately 70 such associations have been identified. 1 -3,5 The ABO antigens are glycol proteins found throughout the body, possibly even in bone tissue, which suggests that there might be a biological connection between ABO blood groups and osteoporosis.…”
Section: B-b Lu K-h LI Abo Blood Groups and Osteoporosis Severitymentioning
confidence: 99%
“…4 The activation of the ABO promoter appears to be influenced by the binding of Sp1 or Sp1-like protein(s) in both erythroid and epithelial cell lineages. 8 Osteoporosis is a common disease with a strong genetic component, which is characterized by low bone mass, microarchitectural deterioration of the bone tissue and an increased risk of fracture. 11 Twin and family studies have shown that genetic factors play an important role in regulating BMD.…”
Section: B-b Lu K-h LI Abo Blood Groups and Osteoporosis Severitymentioning
confidence: 99%